The Historical and Human Existence of Jesus in Paul's Letters - Gathercole, Simon J. 1974- (2018)
The present article seeks to show that the case for the mythical Jesus is seriously undermined by the evidence of the undisputed Pauline epistles. By way of a thought experiment, these letters are taken in isolation from other early Christian literature, and are discussed in dialogue with mythicist scholarship. Attention to the language of the birth, ancestry and coming of Jesus demonstrates the historicity and human bodily existence of Jesus. There is also information about his ministry, disciples, teaching and character in the epistles which has been neglected. Paul's letters, even taken alone, also show the Herodian timeframe of Jesus' ministry. The evidence discussed challenges not only mythicist hypotheses, but also the minimalist strand of more mainstream Jesus-Paul research.
Keywords: Jesus; Paul; Historicity; Humanity; mythicism